Download presentation
Presentation is loading. Please wait.
1
11.7 – Proof by Mathematical Induction
2
Mathematical induction is a method of proving statements involving natural numbers.
3
Mathematical induction is a method of proving statements involving natural numbers.
To prove a statement true for all natural numbers, n:
4
Mathematical induction is a method of proving statements involving natural numbers.
To prove a statement true for all natural numbers, n: 1. Show that the statement is true for n = 1
5
Mathematical induction is a method of proving statements involving natural numbers.
To prove a statement true for all natural numbers, n: 1. Show that the statement is true for n = 1 2. Assume that the statement is true for some natural number, k. (induction hypothesis)
6
Mathematical induction is a method of proving statements involving natural numbers.
To prove a statement true for all natural numbers, n: 1. Show that the statement is true for n = 1 2. Assume that the statement is true for some natural number, k. (induction hypothesis) 3. Show that the statement is true for the next natural number, k + 1.
7
Ex. 1 Prove that 13 + 23 + 33 + … + n3 = n2(n+1)2 4
8
Ex. 1 Prove that 13 + 23 + 33 + … + n3 = n2(n+1)2 4 1
Ex. 1 Prove that … + n3 = n2(n+1) Show that the statement is true for n = 1.
9
Ex. 1 Prove that 13 + 23 + 33 + … + n3 = n2(n+1)2 4 1
Ex. 1 Prove that … + n3 = n2(n+1) Show that the statement is true for n = … + n3 = n2(n+1)2
10
Ex. 1 Prove that 13 + 23 + 33 + … + n3 = n2(n+1)2 4 1
Ex. 1 Prove that … + n3 = n2(n+1) Show that the statement is true for n = … + n3 = n2(n+1)2 n = 1:
11
Ex. 1 Prove that 13 + 23 + 33 + … + n3 = n2(n+1)2 4 1
Ex. 1 Prove that … + n3 = n2(n+1) Show that the statement is true for n = … + n3 = n2(n+1)2 n = 1: 13= 12(1+1)2
12
Ex. 1 Prove that 13 + 23 + 33 + … + n3 = n2(n+1)2 4 1
Ex. 1 Prove that … + n3 = n2(n+1) Show that the statement is true for n = … + n3 = n2(n+1)2 n = 1: 13= 12(1+1)2
13
Ex. 1 Prove that 13 + 23 + 33 + … + n3 = n2(n+1)2 4 1
Ex. 1 Prove that … + n3 = n2(n+1) Show that the statement is true for n = … + n3 = n2(n+1)2 n = 1: 13= 12(1+1)2 1 = 1(2)2
14
Ex. 1 Prove that 13 + 23 + 33 + … + n3 = n2(n+1)2 4 1
Ex. 1 Prove that … + n3 = n2(n+1) Show that the statement is true for n = … + n3 = n2(n+1)2 n = 1: 13= 12(1+1)2 1 = 1(2)2 1 = 1, thus shown to be true.
15
2. Assume that the statement is true for some natural number, k.
16
2. Assume that the statement is true for some natural number, k
2. Assume that the statement is true for some natural number, k … + n3 = n2(n+1)2 4
17
2. Assume that the statement is true for some natural number, k
2. Assume that the statement is true for some natural number, k … + n3 = n2(n+1) … + k3 = k2(k+1)2
18
3. Show that the statement is true for the next natural number, k + 1.
19
3. Show that the statement is true for the next natural number, k + 1
3. Show that the statement is true for the next natural number, k … + k3 = k2(k+1)2 4
20
3. Show that the statement is true for the next natural number, k + 1
3. Show that the statement is true for the next natural number, k … + k3 = k2(k+1) … + k3 + (k+1)3 = k2(k+1)2 + (k+1)3
21
3. Show that the statement is true for the next natural number, k + 1
3. Show that the statement is true for the next natural number, k … + k3 = k2(k+1) … + k3 + (k+1)3 = k2(k+1)2 + (k+1)3 = k2(k+1)2 + (k+1)3 4 1
22
3. Show that the statement is true for the next natural number, k + 1
3. Show that the statement is true for the next natural number, k … + k3 = k2(k+1) … + k3 + (k+1)3 = k2(k+1)2 + (k+1)3 = k2(k+1)2 + (k+1)
23
3. Show that the statement is true for the next natural number, k + 1
3. Show that the statement is true for the next natural number, k … + k3 = k2(k+1) … + k3 + (k+1)3 = k2(k+1)2 + (k+1)3 = k2(k+1)2 + (k+1) = k2(k+1)2 + 4(k+1)3 4 4
24
= k2(k+1)2 + 4(k+1)3 4
25
= k2(k+1)2 + 4(k+1)3 4 = (k+1)2 [k2 + 4(k+1)]
26
= k2(k+1)2 + 4(k+1)3 4 = (k+1)2 [k2 + 4(k+1)] = (k+1)2 [k2 + 4k+4]
27
= k2(k+1)2 + 4(k+1)3 4 = (k+1)2 [k2 + 4(k+1)] = (k+1)2 [k2 + 4k+4] = (k+1)2 (k+2)2 4
28
= k2(k+1)2 + 4(k+1)3 4 = (k+1)2 [k2 + 4(k+1)] = (k+1)2 [k2 + 4k+4] = (k+1)2 (k+2) … + k3 + (k+1)3 = (k+1)2 (k+2)2 4
29
So we started with the problem:
… + n3 = n2(n+1)2 4
30
So we started with the problem:
… + n3 = n2(n+1)2 4 And we showed: … + k3 + (k+1)3 = (k+1)2 (k+2)
31
So we started with the problem:
… + n3 = n2(n+1)2 4 And we showed: … + k3 + (k+1)3 = (k+1)2 (k+2) So we proved that the statement holds true when we replace n with k + 1 and thus proven.
32
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2
33
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1:
34
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1: 12 = 1(3∙1 – 1) 2
35
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1: 12 = 1(3∙1 – 1) 2 1 = 1
36
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1: 12 = 1(3∙1 – 1) 2 1 = 1 n = 2:
37
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1: 12 = 1(3∙1 – 1) 2 1 = 1 n = 2: = 2(3∙2 – 1) 2
38
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1: 12 = 1(3∙1 – 1) 2 1 = 1 n = 2: = 2(3∙2 – 1) 2 5 = 5
39
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1: 12 = 1(3∙1 – 1) 2 1 = 1 n = 2: = 2(3∙2 – 1) 2 5 = 5 n = 3:
40
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1: 12 = 1(3∙1 – 1) 2 1 = 1 n = 2: = 2(3∙2 – 1) 2 5 = 5 n = 3: = 3(3∙3 – 1) 2
41
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1: 12 = 1(3∙1 – 1) 2 1 = 1 n = 2: = 2(3∙2 – 1) 2 5 = 5 n = 3: = 3(3∙3 – 1) 2 14 = 12
42
Ex. 2 Find a counterexample to disprove the statement
Ex. 2 Find a counterexample to disprove the statement … + n2 = n(3n – 1) 2 n = 1: 12 = 1(3∙1 – 1) 2 1 = 1 n = 2: = 2(3∙2 – 1) 2 5 = 5 n = 3: = 3(3∙3 – 1) 2 14 = 12, FALSE
43
n = 3 Ex. 2 Find a counterexample to disprove the statement.
… + n2 = n(3n – 1) n = 1: 12 = 1(3∙1 – 1) 1 = 1 n = 2: = 2(3∙2 – 1) 5 = 5 n = 3: = 3(3∙3 – 1) 14 = 12, FALSE n = 3
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.